The impact of non-audit services on auditor independence and audit quality: risks, regulations, and ethical considerations - Ramlan, Nur Syafiqah Balqis; Hassan, Rabaatul Azira (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
The granting of non-audit services (NAS) has been regarded as a controversial area for audit firms in respect to how it might influence their independence and the quality of auditing. Some claim that NAS enables positive spillovers and therefore enhances the quality of audits, whereas others contend that it creates economic dependencies that are detrimental to the objectivity of the auditor. This study analyzes the contradictory effect of NAS with an emphasis on financial dependences and threats to self-interest and self-review as professional scepticism and the justification of bias become easier and more prevalent than the audit outcomes question independence. There is a divide among the jurisdictions on how to respond to NAS, with some being more aggressive in their prohibition while others apply a softer touch allowing a controlled amount of NAS under tighter supervision. There are gaps in existing empirical literature, suggesting that the overwhelming NAS approach to audit quality is too simplistic without considering governance systems, and laws. This study highlights the need for more definitive answers to justify the power of NAS with stronger policy guidance and negative NAS disclosures and NAS in general. It calls for a reconsideration of existing frameworks to ensure that independence of the auditors is guaranteed while guaranteeing that the quality of audit work does not diminish.